Analisis Gerak Tari Ulu Ambek Di Nagari Sintuk Kecamatan Sintuk Toboh Gadang Kabupaten Padang Pariaman: Aspek Ruang, Waktu, Dan Tenaga - Nilam Permata Sari; Darmawati Darmawati (FBS Universitas Negeri Padang, 2019)
This article aims to reveal and describe the form of motion analysis of Ulu Ambek dance in Nagari Sintuk subdistrict Sintuk Toboh Gadang District Padang Pariaman Judging by aspects of space, time, and energy. This type of research is qualitative research with a descriptive method. The main instrument in this research is its own researchers and assisted with supporting instruments such as mobile stationery and digital cameras. The data types in this study are primary data and secondary data. Data collection techniques are conducted by means of interviews, observations and documentation. The steps in analyzing data are data collection, data reduction, data presentation and withdrawal of conclusions. The results showed that Tari Ulu Ambek is a tradition art that at present is only shown as a form of the sylladance of the community between Nagari in Pariaman. The motion of Tari Ulu Ambek is 1) The motion of the Harvest, (2) The motion of the past (attacking), (3) Motion of Ambek (repelling), (4) The motion of Tigo, (5) The motion of Anggua, (6) Movements of the Tari Ulu Ambek has motion analysis based on space, time, and energy aspects. Although the movement is not structured neatly, but it can still be seen the aspect of space, time, and energy from Ulu Ambek dance.